2016
DOI: 10.1186/s12889-016-3894-z
|View full text |Cite
|
Sign up to set email alerts
|

An equity analysis of utilization of health services in Afghanistan using a national household survey

Abstract: BackgroundAfghanistan has made great strides in the coverage of health services across the country but coverage of key indicators remains low nationally and whether the poorest households are accessing these services is not well understood.MethodsWe analyzed the Afghanistan Mortality Survey 2010 on utilization of inpatient and outpatient care, institutional delivery and antenatal care by wealth quintiles. Concentration indexes (CIs) were generated to measure the inequality of using the four services. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 37 publications
7
36
0
Order By: Relevance
“…Equitable utilization of healthcare services for those in need without suffering from financial hardship has been emphasized in the universal health coverage (UHC) paradigm [1][2][3]. This matter has also been reemphasized in Sustainable Development Goals to ensure healthy lives and well-being promotion for all and at all ages [4].…”
Section: Introductionmentioning
confidence: 99%
“…Equitable utilization of healthcare services for those in need without suffering from financial hardship has been emphasized in the universal health coverage (UHC) paradigm [1][2][3]. This matter has also been reemphasized in Sustainable Development Goals to ensure healthy lives and well-being promotion for all and at all ages [4].…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of a survey in 2015, Afghan people receive primary and secondary healthcare services through the Basic Package of Health Services and Essential Package of Hospital Services. However, these packages cover only 57% of the population [ 11 ]. In 2009, Amare et al reported that about 60% of Afghan people obtained healthcare services via private hospitals and ambulatory care services [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported unequal health service utilization between the poor people and the wealthy people [ 5 7 ], such as health service utilization being lower in low-income populations than in high-income populations [ 8 11 ], and high quality resource utilization being higher for the wealthy people than the poor people [ 12 , 13 ]. Although economic status, health status, and health policy are all important factors that affect the utilization of health services [ 14 17 ], economic status contributes the most to the huge gap in health service utilization between poor and wealthy women [ 18 ]. Medicare insurance can improve the equity in the utilization of health services to some extent.…”
Section: Introductionmentioning
confidence: 99%